Peaceful End-of-Life-Care Program and Do Not Resuscitate (DNR) orders among nurses: A literature review - M Sobirin Mohtar; Silvi Yanti; Fitri Yuliana (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: One of the emergency cases that often occurs outside the hospital and is often found in the Emergency Room is heart disease which is the first leading cause of death in the world. When nurses apply Peacefulness and life care, that is, nurses are not maximal in providing services due to various factors including the work environment of the Emergency Room with urgent and crowded conditions.Purpose: To identify Peaceful End-of-Life-Care Program and Do Not Resuscitate (DNR) orders among nurses: A literature reviewMethod: This type of literature research or literature review is characterized by descriptive analysis, namely the regular breakdown of the data that has been obtained. The data used in this research is secondary data.Results: In the 10 articles found, there were 5 articles that stated that nurses carried out end-of-life actions peacefully to patients and families. From several reviews of end-of-life care articles, important factors in dying care are reducing pain, involving families in end-of-life care, providing empathy, respecting and respecting patient and family decisions, and respecting the rights of patients and families.Conclusion: Nurse's experience in the peaceful end of life for patients near death, resuscitation, and emergency services. Obtained good results and the peaceful end of life is carried out in patients well.